ENT 530 Case Study: Dolcé / Siti Su'aidah Kaiyisah Sharuddin ... [et al.] - Sharuddin, Siti Su'aidah Kaiyisah; Sherifuddin, Nur Adlyn Sofea; Damla, Nor Syafiqah; Yahya, Erissa Kystiena; Mohd Bahtiar, Nur Dini Syafiqah; Mohd Zaki, Nurul Izzah; Mohd Rosli, Nur Izzati; Jaapar, Nur Syazwien (2021)
Dolcé is a small business that is owned by a young entrepreneur. Dolcé is focusing on selling Melted Cadbury Cookies for cookie lovers where its goal is to introduce affordable and delicious cookies with premium ingredients that could be enjoyed and eaten by everyone. Dolcé produces a cookie that can make all their customers afford to buy their cookies with an affordable price. Due to MCO, Dolcé also gives opportunities to everyone, especially young people to make side income by being a part of Dolcé business. To make sure the business runs and operates smoothly, Dolcé always implements business, marketing, and operational strategies to achieve their business objectives and the goals. Throughout the operation of Dolcé business, they are also facing several major problems and challenges to conducting their business as well. However, they never gave up to pursue this business at a higher level because Dolcé believes that all the problems and challenges need to be listed out so that they know how to overcome the solution from those problems and challenges. Dolcé also uses the various platforms to advertise their product in order to ensure their Melted Cadbury Cookies will be at par with other competitors and the external market. The management of Dolcé is not only sought for profit, but they also consider the long-term of the business.